An Emperical Study on Problems of Investors in Investment Avenues - Agarwal, Varsha (Korea Review of International Studies, 2022)
Investments carry a level of risk since they require the investor to part with money that they have worked hard to earn. An astute investor who has received the appropriate instruction can significantly cut risk while increasing potential returns. There is a wide variety of options available to investors for putting their money to work. The investors anticipate higher returns while taking on a comparably lower level of risk. The goals of the research are to know the demographic elements that influence investment opinion and to examine the investment opportunities available to investors. The study is of an analytical and descriptive character, and it focuses on the investors' perceptions of investment avenues as well as the implications such perceptions have on levels of satisfaction and post-investment behaviour. It is contingent on both primary and secondary sources of information. The outcomes of the study indicated that the opinions of investors on various investment opportunities in Tamil Nadu might be used to better understand investor perceptions.
ISME
Keywords: Investors; Investment Avenues; Income; Savings; Innovation; Globalization; Investment